Using the PEBIC criteria to assess the quality of responses provided during a Family Planning radio program - Fagbemi, Babafunke; Adegbenro, Abiodun; Akande, Toyin; Udennaka, Charles; Uzoh-Ntiwunka, Adaora; Toriola, Bukola; Ayodele, Adenike (Frontiers in Global Women's Health, 2025)
IntroductionRadio remains a dominant source of information, in Sub-Saharan Africa, with 75% of the population relying on it. In Nigeria, radio reaches over 70% of citizens and stands as a vital tool for behavior change. Tailoring radio programs to address needs and cultural contexts of communities has proved essential for building trust and influencing behavioral change. Traditional evaluation of radio interactive programs focus on listener engagement metrics but overlooks the evaluation of the quality of the resource person's responses to the caller's questions. This study aimed to assess the quality of information delivered by resource persons during the interactive segments of a Family Planning (FP) radio program using a criteria.MethodsA qualitative analysis was conducted on caller questions and resource person responses from FP radio programs in three Nigerian states. A customized ranking system based on “Presentation,” “Empathy,” “Provider's Bias elimination,” “Information correctness,” and “Context Specificity” (PEBIC) was used by FP experts to assess the resource person's response quality. The scores for the responses were segmented and categorized into low, moderate and high quality using the mean, and standard deviation then analyzed using SPSS version 20.ResultsFor the technical segment of the radio program, while individually assessing each item on the criteria, the quality of responses was high, with an average of 91.2%. For the entertainment education segment of the radio program, while individually assessing each item on the criteria, the quality of responses with empathy was low (28%), however, the quality of responses for other criteria was high, with an average of 79.8%. Furthermore, in the overall quality of response for the technical segment, the responses given by the resource persons were of high quality (81%) while those of the entertainment education segment were of moderate quality (58%).ConclusionThe radio program excelled in delivering technical information but fell short in fostering adequate empathy during the entertainment education segment. Additional training for resource persons to hone their skills in embedding their message delivery in an empathetic frame thus strengthening the emotive connection with the audience is key. This could significantly improve the program's overall impact.